Ion-conducting membranes based on gelatin and containing LiI/I-2 for electrochromic devices - Ponez, L.; Sentanin, F.C.; Majid, Siti Rohana; Arof, Abdul Kariem; Pawlicka, A. (Taylor & Francis, 2012)
Ionic conducting membranes of gelatin plasticized with glycerol and containing LiI/I-2 have been obtained and characterized by X-ray diffraction measurements, UV-Vis-NIR spectroscopy, thermal analysis and impedance spectroscopy. The transparent (80-90% in the visible range) membranes showed ionic conductivity value of 5 x 10(-5) S/cm at room temperature, which increased to 3 x 10(-3) S/cm at 80 degrees C. All the ionic conductivity measurements as a function of temperature showed VTF dependence and activation energy of 8 kJ/mol. These samples also showed low glass transition temperature of -76 degrees C. Moreover the samples were predominantly amorphous. The membranes applied to small electrochromic devices showed 20% of color change from colored to bleached states during more than 70 cronoamperometric cycles.